2020
DOI: 10.1016/j.ejop.2020.125671
|View full text |Cite
|
Sign up to set email alerts
|

Isolates from ancient permafrost help to elucidate species boundaries in Acanthamoeba castellanii complex (Amoebozoa: Discosea)

Abstract: Acanthamoeba castellanii species complex (genotype T4) comprises of more than ten species with unclear synonymy. Its molecular phylogeny has several conflicts with published morphological data. In this paper, we analyze morphometric traits and temperature preferences in six new strains belonging to A. castellanii complex isolated from Arctic permafrost in the framework of molecular phylogeny. This integrative approach allows us to cross-link genotypic and phenotypic variability and identify species-level bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Since then, many more protozoa have been discovered in permanently frozen environments and further reactivated. These studies confirmed that microbes may survive for long periods of time (sometimes, up to one million years) at subzero temperatures, and in the absence of any oxygen and liquid water (Shatilovich et al 2009 , 2015 ; Stoupin et al 2012 ; Shmakova et al 2016 , 2018 ; Malavin and Shmakova 2020 ). Very recently, Malavin and co-workers reported on the isolation of 35 amoeboid protists from frozen sediments, a discovery that motivated them to propose the existence of a so-called “frozen zoo” (Malavin et al 2020 ).…”
Section: Cryosphere As Reservoir For Past and Present Human Pathogensmentioning
confidence: 75%
“…Since then, many more protozoa have been discovered in permanently frozen environments and further reactivated. These studies confirmed that microbes may survive for long periods of time (sometimes, up to one million years) at subzero temperatures, and in the absence of any oxygen and liquid water (Shatilovich et al 2009 , 2015 ; Stoupin et al 2012 ; Shmakova et al 2016 , 2018 ; Malavin and Shmakova 2020 ). Very recently, Malavin and co-workers reported on the isolation of 35 amoeboid protists from frozen sediments, a discovery that motivated them to propose the existence of a so-called “frozen zoo” (Malavin et al 2020 ).…”
Section: Cryosphere As Reservoir For Past and Present Human Pathogensmentioning
confidence: 75%
“…Finally, it is also possible that the genomes of bacteriophages, like that of other viruses, are under-represented because of the use of an inadequate DNA extraction protocol. Regarding eukaryotic viruses, our results are nevertheless less surprising, since they show a predominance for families of viruses infecting protozoa whose presence in ancient permafrost is known (33, 34). In addition, some members of these viral families have been reactivated (23, 24).…”
Section: Discussionmentioning
confidence: 49%
“…7). Live amoeba are routinely isolated from permafrost (33, 34). Except for a small number of contigs associated to Asfarviridae and even less to Iridoviridae, almost no eukaryotic viruses were detected from the families known to infect metazoan organisms, although their metazoan DNA was readily detected in most samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the present time there have been few loci other than the two small subunit rRNA genes for which a substantial number of isolates have been studied. Among the few regions with more than 20 sequences from various isolates are portions of the mitochondrial cytochrome C oxidase subunit I/II gene [ 47 , 48 , 49 , 50 ], the mitochondrial ND5 gene [ 47 ], the large subunit rRNA and the ITS region of the ribosomal RNA complex [ 51 ], the mannose and laminin binding proteins [ 52 ], and a set of 5 proteins: Beta Tubulin ( BETA ), Glycogen Phosphorylase ( GLYP ), Glyceraldehyde-3-phosphate dehydrogenase ( G3PD ), Elongation Factor 1 alpha ( ELF1 ), and RASC [ 53 ].…”
Section: How Reliable Is the Sequence Information For Standard Strain...mentioning
confidence: 99%